A Methodology to Adapt Data Path Architectures to a MIPS-1 Model - Casillo, Leonardo Augusto; Silva, Ivan Saraiva (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2012)
MIPS (Microprocessor without Interlocked Pipeline Stages) is an Instruction Set Architecture used in applications such as computers, routers, game consoles and various embedded systems. Among the advantages of this pattern, it could be cited the variety of free software such as compilers and simulators. This paper shows a methodology required to adapt other architectures to use a MIPS-1 instruction set without significant increase in chip area and power dissipation. This methodology was applied in two case studies, which architectures at different complexity levels data paths will be adapted to a new model.